Characterization of canine adipose tissue‐derived mesenchymal stem cells immortalized by SV40‐T retrovirus for therapeutic use. Issue 9 (19th February 2019) - Ayala‐Cuellar, Ana Patricia; Kim, Cho‐Won; Hwang, Kyung‐A; Kang, Ji‐Houn; Lee, Gabsang; Cho, Jaejin; Choi, Kyung‐Chul
Abstract: Canine mesenchymal stem cells (cMSCs) are gaining popularity in the veterinary field as a regenerative therapy. But, their limited culture lifespan makes it an obstacle for preclinical investigation and therapeutic use. In this study, primary canine adipose tissue‐derived MSCs (PCAT‐MSCs) were isolated from adipose tissue and were transfected with the SV40‐T retrovirus resulting in a life‐extended immortalized canine adipose tissue‐derived MSCs (ICAT‐MSCs). A comparison was made through the characterization of both PCAT‐MSCs and ICAT‐MSCs. Both showed a fibroblastic morphology; ICAT‐MSCs showed a higher potential of colony formation compared with PCAT‐MSCs and a reduced population doubling time; stem cell markers SOX2 and NANOG were expressed in both cell lines; karyotyping analysis showed no abnormalities in both PCAT‐MSCs and ICAT‐MSCs; both cell lines were CD90 +, CD44 +, and CD45 − ; both generated chondrogenic pellet; in osteogenic differentiation both showed upregulation of Osterix, a master transcriptome of osteogenesis, but in PCAT‐MSCs, an upregulation of SOX2 was also observed. In conclusion, ICAT‐MSCs showed similar characteristics with PCAT‐MSCs, thus established as an easy to access platform for studies on better understanding about cMSCs nature. Abstract : Karyotypes of PCAT‐MSCs (A) at P2 and ICAT‐MSCs (B) at P13 were performed by a genome analysis.